2006
DOI: 10.1007/s00787-006-0548-1
|View full text |Cite
|
Sign up to set email alerts
|

The continuity of psychopathology from early childhood to preadolescence

Abstract: The results show the complexity of pathways in psychopathology from early childhood to preadolescence. In particular, aggressive and destructive behaviors in very early childhood predict later problems and necessitate early recognition and possible intervention at an early age. An instrument like the CBCL 2-3 is valuable in the early detection of children at risk of long-term problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
88
0
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 39 publications
6
88
0
7
Order By: Relevance
“…In agreement with earlier findings, we can conclude that delinquent behavior and aggressive behavior tap different constructs and follow distinct developmental pathways (40, 41) insofar as they predict different outcomes. The longitudinal association between externalizing behavior and both later thought problems and somatic complaints have been reported before in young children (40)(41)(42)(43). However, until replicated in future studies that report up to adulthood, these results should be considered preliminary.…”
Section: Discussionmentioning
confidence: 69%
“…In agreement with earlier findings, we can conclude that delinquent behavior and aggressive behavior tap different constructs and follow distinct developmental pathways (40, 41) insofar as they predict different outcomes. The longitudinal association between externalizing behavior and both later thought problems and somatic complaints have been reported before in young children (40)(41)(42)(43). However, until replicated in future studies that report up to adulthood, these results should be considered preliminary.…”
Section: Discussionmentioning
confidence: 69%
“…Furthermore, students who develop a diagnosable disorder often exhibit early indicators (Pihlakoski et al, 2006) that could be identified through systematic screening for emotional and behavioral risk.…”
mentioning
confidence: 99%
“…The notion that persistent aggressiveness in childhood can become violent behavior over time justifi es the need for it to be recognized early (Dessen & Szelbracikowski, 2006) so that, where necessary, appropriate intervention can be performed as soon as possible to promote child health (Pihlakoski et al, 2006). With regard specifi cally to children, the concern with controlling and minimizing aggressive behavior in order to avoid future behavioral problems is increasing.…”
mentioning
confidence: 99%